2002
DOI: 10.1023/a:1015009210639
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Anderson Fabry Disease (AFD) is an extremely painful and debilitating multi-system X-linked disorder due to alpha-galactosidase enzyme deficiency. To date, no baseline data on health-related quality-of-life (HR-QoL) have been reported in males affected with this condition. In this study, 38 males with AFD completed Medical Outcomes Study Short Form, EuroQoL questionnaires and an AFD-specific questionnaire prior to the start of a trial involving replacement therapy with alpha-galactosidase. Results from these q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 9 publications
1
22
1
Order By: Relevance
“…Most studies constrain to comparisons with healthy controls which indicate major impairments in affected patients [ 8 , 9 , 16 , 17 ] and the effects of enzyme replacement therapy on HRQoL. If SF-36 questionnaires were used, the main affected parameter was ‘general health’ [ 9 ]. Moreover, psychiatric diseases and related affections of HRQoL are frequently evident in Fabry patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies constrain to comparisons with healthy controls which indicate major impairments in affected patients [ 8 , 9 , 16 , 17 ] and the effects of enzyme replacement therapy on HRQoL. If SF-36 questionnaires were used, the main affected parameter was ‘general health’ [ 9 ]. Moreover, psychiatric diseases and related affections of HRQoL are frequently evident in Fabry patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested by various studies [ 8 , 9 ] that a history of cardiovascular disease impacts on HRQoL in Fabry patients. We categorized cardiovascular events into minor and major events and found that neither was significantly associated with HRQoL in univariate or multivariate analyses, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small number of studies published before the widespread use of enzyme replacement therapy reported reduced QOL among FD patients, and the authors of those reports suggested that effective treatment with an appropriate agent would have great potential for improving QOL in patients with FD. 18 , 19 Our data on the activities of FD beneficiaries appear to show improvement in the clinical course of FD patients after the start of therapy.…”
Section: Discussionmentioning
confidence: 65%
“…Anxiety is a frequent psychological symptom reported by FD patients [7, 9, 30, 31]. Prevalence estimates in current literature range between 20 and 37% [31, 32].…”
Section: Discussionmentioning
confidence: 99%